Sudden sensorineural hearing loss in children – literature review - Nowak, Monika; Kopeć, Konrad; Drozdowska, Ewa; Dorobisz, Karolina; Zatoński, Tomasz (Pediatria Polska - Polish Journal of Paediatrics, 2022)
Many cases of childhood sudden sensorineural hearing loss (SSNHL) remain debatable and cause both diagnostic and treatment problems. The aim of the study is to recall and collect the latest information about the problem of sudden hearing loss in children. Sudden sensorineural hearing loss in children under 15 years old is rare and its pathophysiology remains unclear. Due to this fact, children’s SSNHL’s clinical characteristics, etiology, treatment outcomes and prognosis have been most likely deemed to be less relevant. There are many factors in children that are able to induce SSNHL, the main ones being viruses, autoimmune and genetic factors. Examination includes tympanometry, audiometry, brainstem responses, as well as radiological testing and laboratory tests. The main treatment applied in this condition is corticosteroids. Prognosis is not promising because nearly half of affected children do not recover.